CHI '06 Extended Abstracts on Human Factors in Computing Systems 2006
DOI: 10.1145/1125451.1125641
|View full text |Cite
|
Sign up to set email alerts
|

A study of the use of mobile phones by older persons

Abstract: This paper reports on issues related to the use of mobile phones by older people. This study uses triangulation, a mixed method of qualitative (focus group discussions) and quantitative (online questionnaire) approaches. Usage patterns, problems, perceived benefits and desired and unwanted features were covered in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 2 publications
(2 reference statements)
5
70
0
1
Order By: Relevance
“…The main objective of this research is to replicate the study performed by Sri Kurniawan et al [6] in a different country. Simultaneously, the focus will be on verifying the relevance of the identified design issues as well as comparing the similarities and difference between the studies.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The main objective of this research is to replicate the study performed by Sri Kurniawan et al [6] in a different country. Simultaneously, the focus will be on verifying the relevance of the identified design issues as well as comparing the similarities and difference between the studies.…”
Section: Methodsmentioning
confidence: 89%
“…Secondly, we get the original questionnaires based on the research [6] and then the questionnaires were distributed to older peoples who are directly using a mobile phone in their daily routines across 14 states in Malaysia. From the questionnaires that have been distributed, 176 older peoples taking part in this survey.…”
Section: Methodsmentioning
confidence: 99%
“…Before the rise of smartphones, in 2006 studies showed that the age group 60+ made limited usage of mobile phones, using them mainly for emergencies [26]. Seniors also seemed to avoid SMS and other communication features, simply because the devices were deemed as not user-friendly: the displays and buttons were small and difficult to see.…”
Section: Seniors' Smartphone Usage Habitsmentioning
confidence: 99%
“…There is confirmatory evidence of older mobile phone users making use of a small subset of core functionality [37], and that their usage is determined by their needs [38]. Turner, Love and Howell found evidence that older users did indeed use their phones less than younger users [39].…”
Section: Fig 10 Factors Impacting On Older Mobile Phone Usersmentioning
confidence: 95%